First permanent molar (6 years molar) edentation: Classic prosthetic rehabilitation versus implant supported prosthetic rehabilitation (preliminary study) - Sorin Nicolae POPESCU; Gabriela TANASE; Gabriel CIOCHINDA; Augustin MIHAI; Viorel Stefan PERIEANU; Ruxandra STANESCU; Iuliana BABIUC; Radu COSTEA; Simion Gh. DUMITRU; Oana-Cella ANDREI; Luminita OANCEA; Mirel TOMA; et al. (Romanian Journal of Medical Practice, 2020)
Introduction. Prosthetic restoration of single tooth edentation produced by the loss of the permanent first molar (6-year molar), regardless of its location (maxillary or mandibular), represents a challenge for any dentist. Purpose. In this study we tried to present some theoretical and practical aspects regarding the advantages of implant-prosthetic rehabilitation, regarding the advantages of implant-prosthetic rehabilitation compared to the classic prosthetic rehabilitation, for the restoration of the 6-year molar single tooth edentation, taking into account both the opinions of the dentists and the preferences of the patients. Material and method. The study was conducted between April 15 and June 30, 2018 on a group of 39 dentists, based on a questionnaire with 8 questions. Results and discussion. The results obtained from the analysis of the answers given to the 8 questions, have been exposed in a varied iconography for easier understanding. Conclusion. The most important aspect of this study is that most practitioners have recommended fixed prosthetic restorations on implant support, because of their superior advantages, compared with fixed prosthetic restorations with aggregation on the teeth bordering the edentulous breach.